Online Optical Tomography System Application Of Charge-Coupled Device (CCD) For Object Detection In Crystal Clear Water - Juliza Jamaludin; Ruzairi Abdul Rahim; Herlina Binti Abdul Rahim; Mohd Hafiz Fazalul Rahiman; Siti Zarina Bte. Mohd Muji; Jemmy Mohd Rohani (JISR on Computing, 2016)
This research presents an application of Charge-Coupled Device (CCD) linear sensor and laser diode in an optical tomography system. These optoelectronic sensors are believed to detect solid objects rather than transparent objects. Based on the research results, the development of optical tomography system using CCD and laser diode has helped to enhance the potential of these sensors in detecting low-opacity objects. Experiments for detecting a solid rod, transparent rod and air bubbles in non-flowing crystal clear water were conducted in this study. From the image reconstruction results, it clearly shows a cross-sectional image of a pipeline system with the existence and the exact location of opaque and transparent objects in multiphase flow detected by the orthogonal projection of CCD sensors and lasers. The information details of real-time multiphase flow that observed by this system can be transmit via wireless or wired data communication system.